La protection constitutionnelle des minorités - Beaudoin, Gérald-A. (Les Cahiers de droit, 1986)
The author outlines areas covered by constitutional texts and in doing so points to various deficiencies. The first one is brought on by the override clause provided in Section 33 of the Charter which makes it possible to suspend certain rights and a second one is found in the fact that the Charter does not deal with social and economic rights, a deficiency which is most likely to be perceived by members of a minority. His observations lead him to conclude that the courts will have to assume an activist role in order to implement various rights.